Deep-Sea Debris in the Central and Western Pacific Ocean - Amon, Diva J.; Kennedy, Brian R. C.; Cantwell, Kasey; Suhre, Kelley; Glickson, Deborah; Shank, Timothy M.; Rotjan, Randi D. (Frontiers in Marine Science, 2020)
Marine debris is a growing problem in the world’s deep oceans. The naturally slow biological and chemical processes operating at depth, coupled with the types of materials that are used commercially, suggest that debris is likely to persist in the deep ocean for long periods of time, ranging from hundreds to thousands of years. However, the realized scale of marine debris accumulation in the deep ocean is unknown due to the logistical, technological, and financial constraints related to deep-ocean exploration. Coordinated deep-water exploration from 2015 to 2017 enabled new insights into the status of deep-sea marine debris throughout the central and western Pacific Basin via ROV expeditions conducted onboard NOAA Ship Okeanos Explorer and RV Falkor. These expeditions included sites in U.S. protected areas and monuments, other Exclusive Economic Zones, international protected areas, and areas beyond national jurisdiction. Metal, glass, plastic, rubber, cloth, fishing gear, and other marine debris were encountered during 17.5% of the 188 dives from 150 m to 6,000 m depth. Correlations were observed between deep-sea debris densities and depth, geological features, and distance from human-settled land. The highest densities occurred off American Samoa and the main Hawaiian Islands. Debris, mostly consisting of fishing gear and plastic, were also observed in most of the large-scale marine protected areas, adding to the growing body of evidence that even deep, remote areas of the ocean are not immune from human impacts. Interactions with and impacts on biological communities were noted, though further study is required to understand the full extent of these impacts. We also discuss potential sources and long-term implications of this debris.